2019
DOI: 10.1177/0271678x19827944
|View full text |Cite
|
Sign up to set email alerts
|

Elevated brain oxygen extraction fraction measured by MRI susceptibility relates to perfusion status in acute ischemic stroke

Abstract: Recent clinical trials of new revascularization therapies in acute ischemic stroke have highlighted the importance of physiological imaging to identify optimal treatments for patients. Oxygen extraction fraction (OEF) is a hallmark of at-risk tissue in stroke, and can be quantified from the susceptibility effect of deoxyhemoglobin molecules in venous blood on MRI phase scans. We measured OEF within cerebral veins using advanced quantitative susceptibility mapping (QSM) MRI reconstructions in 20 acute stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…In a study from 2014(78), Christen et al observed a correlation between areas of decreased oxygen levels as defined by MRI and ex-vivo examination with hypoxia specific biomarkers. Other studies using MRI sequences sensitive to transverse relaxtion have demonstrated how perfusion deficits correlate to increased OEF in AIS patients (77,80). Although highly promising, the qBOLD technique also has challenges such as the need for several examinations and longer examination times than what is necessary with CT.…”
Section: Quantitative Bold In Acute Ischemic Strokementioning
confidence: 99%
“…In a study from 2014(78), Christen et al observed a correlation between areas of decreased oxygen levels as defined by MRI and ex-vivo examination with hypoxia specific biomarkers. Other studies using MRI sequences sensitive to transverse relaxtion have demonstrated how perfusion deficits correlate to increased OEF in AIS patients (77,80). Although highly promising, the qBOLD technique also has challenges such as the need for several examinations and longer examination times than what is necessary with CT.…”
Section: Quantitative Bold In Acute Ischemic Strokementioning
confidence: 99%
“…Cerebral oxygen extraction fraction (OEF) is a potential biomarker in a variety of diseases, such as Alzheimer's disease, 1,2 cerebrovascular diseases, [3][4][5][6][7][8] multiple sclerosis, 9 and sickle cell anemia. 3,[10][11][12] The current gold-standard for image-based OEF quantification inside the human brain is positron emission tomography (PET) with three different 15 O-labeled radiotracers, 13 including 15 O-labeled carbon monoxide (C 15 O) to estimate cerebral blood volume (CBV), 15 O-labeled water (H 2 15 O) to measure cerebral blood flow (CBF), and 15 O-labeled oxygen ( 15 O 2 ) to measure oxygen utilization.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][22][23][24][25][26][27][28] Many of these MRI-based methods have found clinical utility in various diseases. [1][2][3]6,9,29,30 However, few studies have validated MRI-based OEF estimations with gold standard 15 O-PET, 31 which would be important to ensure the accuracy of these methods and facilitate their broader clinical applications. T 2 -relaxation-under-spin-tagging (TRUST) is a widely used MRI technique to measure whole-brain OEF based on the relationship between blood T 2 and oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…As for why the above results are produced, there is no clear reason for this. Some scholars believe that excessive hemodilution may lead to decreased hematocrit and thus affect its oxygen-carrying capacity [20][21][22][23]. In addition, expansion therapy may aggravate cerebral edema in the acute stage of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%